The Role of Covid-19 Information in Social Media on Knowledge and Behavior of the Semarang City Community - Desty, Rani Tiara; Arumsari, Wahyuni (Universitas Negeri Semarang cooperate with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2022)
Background: Social media is one of the fastest ways to deliver information with internet technology. News of COVID-19 is broadcast on various media, one of which is social media. The city of Semarang is in the first place with the largest number of cases in Central Java Province with 95.176. The purpose of this study was to determine the relationship between the quality of COVID-19 information on social media and public response, the relationship between public response to knowledge, and the relationship between knowledge and community behavior regarding COVID-19. Methods: This study uses an analytic observational study with a cross-sectional design. The research sample is Semarang residents who have social media with an age range of 15-65 years. Results: The results showed that there is a significant relationship between the quality of COVID-19 information on social media and public response (p=0,00). There is a significant relationship between public response and knowledge related to COVID-19 (p=0,022). There is a significant relationship between the knowledge and behavior of respondents (p=0,027). Conclusions: Providing valid, specific, and reliable information on social media can improve the behavior of prevention efforts against COVID-19. KEYWORDS: Social media; knowledge; behavior; COVID-19